High-performance damping rubber
By using natural rubber, butyl rubber, nano zinc oxide, carbon black and serpentine powder in shock-absorbing rubber, the problem of limited use of existing shock-absorbing rubber in high temperature and oily media has been solved, and the preparation of high-performance shock-absorbing rubber is achieved, with good heat resistance, shock absorption, water resistance and flame retardant properties.
Patent Information
- Application Number
- CN202411792519.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-07
- Publication Date
- 2025-03-14
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of shock-absorbing rubber, in particular to high-performance shock-absorbing rubber. Background Art
[0002] Vibration is everywhere in real life. Vibration can cause damage to devices, and the noise generated by vibration can seriously affect people's living environment. How to minimize the impact of vibration on human life is the direction pursued by current shock absorption technology. The rubber industry has been committed to controlling and eliminating adverse vibrations. The existing high-quality formulas of shock-absorbing rubber are basically made of natural rubber as the main raw material. However, since natural rubber is not resistant to oil media and has the disadvantage of only being able to withstand 70-80°C, it cannot be used in oil media and high-temperature applications, and its application range is limited. In order to overcome the defects of durability and heat resistance, there are some related records in the prior art of using the high-temperature resistance of nitrile rubber (100-120°C) to prepare shock-absorbing rubber. However, nitrile rubber has the problems of large loss factor (NBR), large delayed heat generation, and poor fatigue resistance. Theoretically, it is not suitable for shock-absorbing materials. Summary of the invention
[0003] The purpose of the present invention is to provide a high-performance shock-absorbing rubber, which has the advantages of high heat resistance and high shock absorption, and solves the problem of poor heat resistance of the shock-absorbing rubber.
[0004] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a high-performance shock-absorbing rubber, characterized in that it comprises the following steps: the high-performance shock-absorbing rubber comprises the following parts by weight: 60-90 parts of natural rubber, 10-30 parts of butadiene rubber, 3-6 parts of nano zinc oxide, 2-4 parts of antioxidant, 10-13 parts of vitrified filler, 1-3 parts of paraffin wax, 15-30 parts of carbon black, 10-25 parts of reinforcing agent, 0.5-1 parts of sulfur, 1-3 parts of composite vulcanizing agent, 1-2 parts of accelerator, 1-2 parts of curing agent, and 1-2 parts of adhesive resin; the reinforcing agent is serpentine powder.
[0005] Preferably, the preparation method of the serpentine powder is as follows: 100 mesh serpentine powder is dispersed in deionized water at a mass ratio of 1: (3-5) of solid-liquid ratio, ultrasonically dispersed for 10-30 minutes while stirring, and then heated to 50-90°C, melamine solution is added to the slurry, and then kept warm for reaction for 5-8 minutes, and then placed in a microwave condition of 100-300W for reaction for 1-3 minutes. After the reaction is completed, the product is dried and crushed.
[0006] Preferably, the preparation method of the nano zinc oxide is as follows: 8-12 parts by weight of zinc acetate and 4-8 parts by weight of zinc sulfate are added to 100 parts by weight of water, and stirred to dissolve to obtain a mixed solution A; 10-15 parts by weight of sodium carbonate or potassium carbonate are dissolved in 100 parts by weight of water, and stirred to dissolve to obtain a mixed solution B; while stirring, the mixed solution B is added to the mixed solution A, and the addition rate of the mixed solution B is controlled to be 1-2mL / min, and then the temperature is increased while stirring. In the initial stage, the heating rate is controlled at 4-8°C / min. After the temperature reaches 55°C, the heating rate is controlled at 1-3°C / min. After the temperature reaches 70°C, the heating is stopped and the temperature is kept warm to obtain a sol containing zinc hydroxide and basic zinc carbonate precipitate; 10-15 parts by weight of ammonia water is added to the sol, and the sol is left to stand for 2-3h, and then dried, and the dried product is calcined at 700-800°C to obtain nano zinc oxide.
[0007] Preferably, the preparation method of carbon black comprises the following steps: adding 30-40 parts by weight of ethanol to 100 parts by weight of water to obtain a dispersion; adding 4-8 parts by weight of quick-pressed black to the dispersion, ultrasonically oscillating until uniformly dispersed, to obtain a mixed solution C; adding 10-20 parts by weight of vinyltrimethoxysilane and 4-6 parts by weight of an organic acid to the mixed solution C, stirring evenly and reacting for 2-3 hours, then adjusting the pH to 6-7, heating in a water bath at 35-40°C for 3-5 hours, and then washing, drying, and grinding to obtain carbon black.
[0008] A method for preparing high-performance shock-absorbing rubber comprises the following steps: A. Mix the vitrifiable filler and reinforcing agent, heat to 500-700°C, keep warm for 30-45 minutes, grind until it passes through a 600-mesh sieve, and then use plasma treatment for 3-7 minutes; B. First, natural rubber, cis-1,4-butadiene rubber, nano zinc oxide and adhesive resin are put into an internal mixer, and plasticized at a temperature of 70 to 110°C for 8 to 20 minutes. Then, light antioxidant, paraffin wax, carbon black, reinforcing agent, composite vulcanizing agent and curing agent are put into the internal mixer, and mixed at a temperature of 120 to 140°C for 8 to 15 minutes, and then cooled to room temperature for discharge; C. Using a double-roll mill, add the product of step B and a flux at 63-68°C, heat to 160-170°C and mix for 45-50min, then add the product of step A, cool to 110-130°C, vacuum mix for 1-2h, and cool naturally to obtain a masterbatch; D. Then, the master rubber in step C is rolled, and after the rubber layer is smooth, a vulcanization accelerator and sulfur are added, and the mixture is rolled into a triangle and then rolled into a thin roll to obtain a mixed rubber; and the mixed rubber is vulcanized at high temperature to obtain a shock-absorbing rubber.
[0009] Preferably, the process conditions of the plasma treatment are: nitrogen is the treatment substance, the treatment power is 200-300W, and the nitrogen flow rate is 0.1-0.2NL / min.
[0010] Preferably, the vacuum mixing has a vacuum pressure of -0.05Mpa to -0.02Mp.
[0011] Preferably, the vulcanization is performed on a flat vulcanizing press at 170-190°C and 8-16MPa for 5-20min.
[0012] Compared with the prior art, the present invention has the following beneficial effects: The present invention arranges serpentine powder as a reinforcing agent, so that the silicone rubber has good water resistance and hydrophobicity, inhibits the adsorption effect of hydrophilic functional groups on water, and also has a fluxing effect, which can reduce the melting point of the mixture in the preparation process. The present invention arranges nano zinc oxide, and the compatibility of nano zinc oxide and basic rubber material is improved, thereby improving the dispersibility of modified nano zinc oxide in the basic rubber material, improving the cross-linking structure of the shock-absorbing rubber, and further improving the heat aging resistance of the shock-absorbing rubber while improving the shock-absorbing performance of the shock-absorbing rubber. The present invention arranges carbon black, which can improve the thermal stability and flame retardancy and fire resistance of the silicone rubber material, can effectively reduce the vulcanization time, improve its processing performance, and improve the anti-ignition ability. The introduction of carbon black into the rubber matrix also has a gas barrier effect, which can prevent the infiltration of air. DETAILED DESCRIPTION
[0013] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0014] The invention provides a technical solution: a high-performance shock-absorbing rubber, comprising the following steps: the high-performance shock-absorbing rubber comprises the following parts by weight: 60-90 parts of natural rubber, 10-30 parts of butadiene rubber, 3-6 parts of nano zinc oxide, 2-4 parts of antioxidant, 10-13 parts of vitrified filler, 1-3 parts of paraffin wax, 15-30 parts of carbon black, 10-25 parts of reinforcing agent, 0.5-1 part of sulfur, 1-3 parts of composite vulcanizing agent, 1-2 parts of accelerator, 1-2 parts of curing agent and 1-2 parts of adhesive resin; the reinforcing agent is serpentine powder.
[0015] The preparation method of serpentine powder is as follows: 100 mesh serpentine powder is dispersed in deionized water at a mass ratio of 1: (3-5) of solid-liquid ratio, and ultrasonic dispersion is performed for 10-30 minutes while stirring, and then the slurry is heated to 50-90°C, and melamine solution is added to the slurry, and then the slurry is kept warm for reaction for 5-8 minutes, and then placed in a microwave condition of 100-300W for reaction for 1-3 minutes. After the reaction is completed, the product is dried and crushed.
[0016] The preparation method of nano zinc oxide is as follows: 8-12 parts by weight of zinc acetate and 4-8 parts by weight of zinc sulfate are added to 100 parts by weight of water, and mixed solution A is prepared after stirring and dissolving; 10-15 parts by weight of sodium carbonate or potassium carbonate are dissolved in 100 parts by weight of water, and mixed solution B is prepared after stirring and dissolving; mixed solution B is added to mixed solution A while stirring, and the adding speed of mixed solution B is controlled to be 1-2mL / min, and then the temperature is increased while stirring, in the initial stage, the heating rate is controlled to be 4-8°C / min, after the temperature reaches 55°C, the heating rate is controlled to be 1-3°C / min, after the temperature reaches 70°C, the heating is stopped, and the temperature is kept warm to obtain a sol containing zinc hydroxide and basic zinc carbonate precipitation; 10-15 parts by weight of ammonia water is added to the sol, and the sol is left to stand for 2-3h, and then dried, and the dried product is calcined at 700-800°C to obtain nano zinc oxide.
[0017] The preparation method of carbon black comprises the following steps: adding 30-40 parts by weight of ethanol to 100 parts by weight of water to prepare a dispersion; adding 4-8 parts by weight of quick-pressed black to the dispersion, and ultrasonically oscillating until uniformly dispersed to prepare a mixed solution C; adding 10-20 parts by weight of vinyltrimethoxysilane and 4-6 parts by weight of an organic acid to the mixed solution C, stirring evenly, reacting for 2-3 hours, then adjusting the pH to 6-7, heating in a water bath at 35-40°C for 3-5 hours, and then washing, drying and grinding to obtain the carbon black.
[0018] A method for preparing high-performance shock-absorbing rubber comprises the following steps: A. Mix the vitrifiable filler and reinforcing agent, heat to 500-700°C, keep warm for 30-45 minutes, grind until it passes through a 600-mesh sieve, and then use plasma treatment for 3-7 minutes; B. First, natural rubber, cis-1,4-butadiene rubber, nano zinc oxide and adhesive resin are put into an internal mixer, and plasticized at a temperature of 70 to 110°C for 8 to 20 minutes. Then, light antioxidant, paraffin wax, carbon black, reinforcing agent, composite vulcanizing agent and curing agent are put into the internal mixer, and mixed at a temperature of 120 to 140°C for 8 to 15 minutes, and then cooled to room temperature for discharge; C. Using a double-roll mill, add the product of step B and a flux at 63-68°C, heat to 160-170°C and mix for 45-50min, then add the product of step A, cool to 110-130°C, vacuum mix for 1-2h, and cool naturally to obtain a masterbatch; D. Then roll the master rubber in step C, add vulcanization accelerator and sulfur after the rubber layer is smooth, make triangle packing and thin pass, and start refining to obtain mixed rubber; vulcanize the mixed rubber at high temperature to obtain shock-absorbing rubber. Embodiment 1:
[0019] A high-performance shock-absorbing rubber; comprising the following parts by weight: 60 parts of natural rubber, 10 parts of butadiene rubber, 3 parts of nano zinc oxide, 2 parts of antioxidant, 10 parts of vitrified filler, 1 part of paraffin wax, 15 parts of carbon black, 10 parts of reinforcing agent, 0.5 parts of sulfur, 1 part of composite vulcanizing agent, 1 part of accelerator, 1 part of curing agent, and 1 part of adhesive resin; the reinforcing agent is serpentine powder; the preparation method of the serpentine powder is: dispersing 100-mesh serpentine powder in deionized water at a mass ratio of 1:3 between material and liquid, stirring and ultrasonically separating the serpentine powder; The mixture was stirred for 10 minutes, and then heated to 50°C, melamine solution was added to the slurry, and then the mixture was kept warm for 5 minutes, and then placed under 100W microwave conditions for 1 minute. After the reaction was completed, the product was dried and crushed; the preparation method of nano zinc oxide is as follows: 8 parts by weight of zinc acetate and 4 parts by weight of zinc sulfate were added to 100 parts by weight of water, and mixed solution A was prepared after stirring and dissolving; 10 parts by weight of sodium carbonate or potassium carbonate were dissolved in 100 parts by weight of water, and mixed solution B was prepared after stirring and dissolving; mixed solution B was added to mixed solution A while stirring, and the addition speed of mixed solution B was controlled to be 1mL / min, and then the mixture was heated while stirring. In the initial stage, the heating rate was controlled at 4°C / min. After the temperature reached 55°C, the heating rate was controlled at 1°C / min. After the temperature reached 70°C, the heating was stopped and the temperature was kept warm to obtain a sol containing zinc hydroxide and basic zinc carbonate precipitation; 10 parts by weight of ammonia water was added to the sol, and the mixture was allowed to stand for 2 hours, and then dried, and the dried product was dried at 400 °C. Calcination at 700°C to obtain nano zinc oxide; the preparation method of carbon black comprises the following steps: adding 30 parts by weight of ethanol to 100 parts by weight of water to obtain a dispersion; adding 4 parts by weight of quick-pressed black to the dispersion, and ultrasonically oscillating until uniformly dispersed to obtain a mixed solution C; adding 10 parts by weight of vinyltrimethoxysilane and 4 parts by weight of an organic acid to the mixed solution C, stirring evenly and reacting for 2 hours, then adjusting the pH to 6, heating in a water bath at 35°C for 3 hours, and then washing, drying, and grinding to obtain carbon black.
[0020] A method for preparing high-performance shock-absorbing rubber comprises the following steps: mixing a vitrified filler and a reinforcing agent, heating the mixture to 500°C, and heat-treating the mixture for 30 minutes, grinding the mixture to pass a 600-mesh sieve, and then treating the mixture with plasma for 3 minutes; B. firstly putting natural rubber, butadiene rubber, nano zinc oxide and adhesive resin into an internal mixer, and plasticizing the mixture at a temperature of 70°C for 8 minutes; then putting a light antioxidant, paraffin wax, carbon black, a reinforcing agent, a composite vulcanizing agent and a curing agent into the internal mixer, and plasticizing the mixture at a temperature of 120°C for 8 minutes; C. firstly putting natural rubber, butadiene rubber, nano zinc oxide and adhesive resin into an internal mixer, and plasticizing the mixture at a temperature of 70°C for 8 minutes; and finally plasticizing the mixture at a temperature of 120°C for 8 minutes. °C, mixing for 8 minutes, cooling to room temperature and discharging; C, using a double-roll mill, adding the product of step B and a flux at 63 °C, heating to 160 °C and mixing for 45 minutes, then adding the product of step A, cooling to 110 °C, vacuum mixing for 1 hour, and naturally cooling to obtain a masterbatch; D, then rolling the masterbatch in step C, after the rubber layer is smooth, adding a vulcanization accelerator and sulfur, making a triangle thin package, and mixing to obtain a mixed rubber; vulcanizing the mixed rubber at high temperature to obtain a shock-absorbing rubber. Embodiment 2:
[0021] In the first embodiment, the following steps are added: A high-performance shock-absorbing rubber; comprising the following parts by weight: 90 parts of natural rubber, 30 parts of butadiene rubber, 6 parts of nano zinc oxide, 4 parts of antioxidant, 13 parts of vitrified filler, 3 parts of paraffin wax, 30 parts of carbon black, 125 parts of reinforcing agent, 1 part of sulfur, 3 parts of composite vulcanizing agent, 2 parts of accelerator, 2 parts of curing agent, and 2 parts of adhesive resin; the reinforcing agent is serpentine powder; the preparation method of the serpentine powder is: dispersing 100 mesh serpentine powder in deionized water at a mass ratio of 1:3 between the material and the liquid, stirring and ultrasonically dispersing 10min, then heated to 50°C, added melamine solution to the slurry, then kept warm for reaction for 5min, then placed in a 100W microwave for reaction for 1min, after the reaction was completed, the product was dried and crushed; the preparation method of nano zinc oxide is as follows: 8 parts by weight of zinc acetate and 4 parts by weight of zinc sulfate are added to 100 parts by weight of water, and a mixed solution A is prepared after stirring and dissolving; 10 parts by weight of sodium carbonate or potassium carbonate are dissolved in 100 parts by weight of water, and a mixed solution B is prepared after stirring and dissolving; mixed solution B is added to mixed solution A while stirring, and the addition speed of mixed solution B is controlled to be 1mL / min, and then the temperature is heated while stirring. In the initial stage, the heating rate is controlled at 4°C / min. After the temperature reaches 55°C, the heating rate is controlled at 1°C / min. After the temperature reaches 70°C, the heating is stopped and the temperature is continued to be kept warm to obtain a sol containing zinc hydroxide and basic zinc carbonate precipitate; 10 parts by weight of ammonia water is added to the sol, and the sol is allowed to stand for 2h, and then dried, and the dried product is dried at Calcination at 700°C to obtain nano zinc oxide; the preparation method of carbon black comprises the following steps: adding 30 parts by weight of ethanol to 100 parts by weight of water to obtain a dispersion; adding 4 parts by weight of quick-pressed black to the dispersion, and ultrasonically oscillating until uniformly dispersed to obtain a mixed solution C; adding 10 parts by weight of vinyltrimethoxysilane and 4 parts by weight of an organic acid to the mixed solution C, stirring evenly and reacting for 2 hours, then adjusting the pH to 6, heating in a water bath at 35°C for 3 hours, and then washing, drying, and grinding to obtain carbon black.
[0022] A method for preparing high-performance shock-absorbing rubber comprises the following steps: mixing a vitrified filler and a reinforcing agent, heating the mixture to 500°C, and heat-treating the mixture for 30 minutes, grinding the mixture to pass a 600-mesh sieve, and then treating the mixture with plasma for 3 minutes; B. firstly putting natural rubber, butadiene rubber, nano zinc oxide and adhesive resin into an internal mixer, and plasticizing the mixture at a temperature of 70°C for 8 minutes; then putting a light antioxidant, paraffin wax, carbon black, a reinforcing agent, a composite vulcanizing agent and a curing agent into the internal mixer, and plasticizing the mixture at a temperature of 120°C for 8 minutes; C. firstly putting natural rubber, butadiene rubber, nano zinc oxide and adhesive resin into an internal mixer, and plasticizing the mixture at a temperature of 70°C for 8 minutes; and finally plasticizing the mixture at a temperature of 120°C for 8 minutes. °C, mixing for 8 minutes, cooling to room temperature and discharging; C, using a double-roll mill, adding the product of step B and a flux at 63 °C, heating to 160 °C and mixing for 45 minutes, then adding the product of step A, cooling to 110 °C, vacuum mixing for 1 hour, and naturally cooling to obtain a masterbatch; D, then rolling the masterbatch in step C, after the rubber layer is smooth, adding a vulcanization accelerator and sulfur, making a triangle thin package, and mixing to obtain a mixed rubber; vulcanizing the mixed rubber at high temperature to obtain a shock-absorbing rubber. Embodiment three:
[0023] In the second embodiment, the following steps are added: a high-performance shock-absorbing rubber; comprising the following parts by weight: 60 parts of natural rubber, 10 parts of butadiene rubber, 3 parts of nano zinc oxide, 2 parts of antioxidant, 10 parts of vitrified filler, 1 part of paraffin wax, 15 parts of carbon black, 10 parts of reinforcing agent, 0.5 parts of sulfur, 1 part of composite vulcanizing agent, 1 part of accelerator, 1 part of curing agent, and 1 part of adhesive resin; the reinforcing agent is serpentine powder; the preparation method of serpentine powder is: disperse 100 mesh serpentine powder in deionized water at a mass ratio of 1:5. The mixture was added into water, ultrasonically dispersed for 30 minutes while stirring, then heated to 90°C, melamine solution was added to the slurry, and then kept warm for reaction for 8 minutes, and then placed under 300W microwave conditions for reaction for 3 minutes. After the reaction was completed, the product was dried and crushed; the preparation method of nano zinc oxide is as follows: 12 parts by weight of zinc acetate and 8 parts by weight of zinc sulfate were added to 100 parts by weight of water, and mixed solution A was prepared after stirring and dissolving; 115 parts by weight of sodium carbonate or potassium carbonate were dissolved in 100 parts by weight of water, and stirred and dissolved to prepare Mixed solution B is obtained; mixed solution B is added to mixed solution A while stirring, and the adding speed of mixed solution B is controlled to be 2 mL / min, and then the temperature is increased while stirring. In the initial stage, the heating rate is controlled at 8°C / min. After the temperature reaches 55°C, the heating rate is controlled at 3°C / min. After the temperature reaches 70°C, the heating is stopped and the temperature is kept warm to obtain a sol containing zinc hydroxide and basic zinc carbonate precipitate; 15 parts by weight of ammonia water is added to the sol, and the sol is allowed to stand for 2-3 hours, and then dried, and The dried product is calcined at 800°C to obtain nano zinc oxide. The preparation method of carbon black comprises the following steps: adding 40 parts by weight of ethanol to 100 parts by weight of water to obtain a dispersion; adding 8 parts by weight of quick-pressed black to the dispersion, and ultrasonically oscillating until uniformly dispersed to obtain a mixed solution C; adding 20 parts by weight of vinyltrimethoxysilane and 6 parts by weight of an organic acid to the mixed solution C, stirring evenly and reacting for 3 hours, then adjusting the pH to 7, heating in a water bath at 40°C for 5 hours, and then washing, drying, and grinding to obtain carbon black.
[0024] A method for preparing high-performance shock-absorbing rubber comprises the following steps: mixing a vitrified filler and a reinforcing agent, heating the mixture to 500°C, and heat-treating the mixture for 30 minutes, grinding the mixture to pass a 600-mesh sieve, and then treating the mixture with plasma for 3 minutes; B. firstly putting natural rubber, butadiene rubber, nano zinc oxide and adhesive resin into an internal mixer, and plasticizing the mixture at a temperature of 70°C for 8 minutes; then putting a light antioxidant, paraffin wax, carbon black, a reinforcing agent, a composite vulcanizing agent and a curing agent into the internal mixer, and plasticizing the mixture at a temperature of 120°C for 8 minutes; C. firstly putting natural rubber, butadiene rubber, nano zinc oxide and adhesive resin into an internal mixer, and plasticizing the mixture at a temperature of 70°C for 8 minutes; and finally plasticizing the mixture at a temperature of 120°C for 8 minutes. °C, mixing for 8 minutes, cooling to room temperature and discharging; C, using a double-roll mill, adding the product of step B and a flux at 63 °C, heating to 160 °C and mixing for 45 minutes, then adding the product of step A, cooling to 110 °C, vacuum mixing for 1 hour, and naturally cooling to obtain a masterbatch; D, then rolling the masterbatch in step C, after the rubber layer is smooth, adding a vulcanization accelerator and sulfur, making a triangle thin package, and mixing to obtain a mixed rubber; vulcanizing the mixed rubber at high temperature to obtain a shock-absorbing rubber. Embodiment 4:
[0025] In Example 3, the following steps are added: a high-performance shock-absorbing rubber; comprising the following parts by weight: 90 parts of natural rubber, 30 parts of butadiene rubber, 6 parts of nano zinc oxide, 4 parts of antioxidant, 13 parts of vitrified filler, 3 parts of paraffin wax, 30 parts of carbon black, 125 parts of reinforcing agent, 1 part of sulfur, 3 parts of composite vulcanizing agent, 2 parts of accelerator, 2 parts of curing agent, and 2 parts of adhesive resin; the reinforcing agent is serpentine powder; the preparation method of serpentine powder is: disperse 100 mesh serpentine powder in deionized water at a mass ratio of 1:5 of material to liquid The mixture was ultrasonically dispersed for 30 minutes while stirring, and then the temperature was raised to 90°C, and the melamine solution was added to the slurry, and then the mixture was kept warm for 8 minutes, and then placed under a 300W microwave for 3 minutes. After the reaction was completed, the product was dried and crushed; the preparation method of nano zinc oxide is as follows: 12 parts by weight of zinc acetate and 8 parts by weight of zinc sulfate were added to 100 parts by weight of water, and mixed solution A was prepared after stirring and dissolving; 115 parts by weight of sodium carbonate or potassium carbonate were dissolved in 100 parts by weight of water, and mixed solution A was prepared after stirring and dissolving Mixed solution B; adding mixed solution B to mixed solution A while stirring, controlling the adding speed of mixed solution B to be 2 mL / min, and then heating while stirring. In the initial stage, the heating rate is controlled at 8°C / min. After the temperature reaches 55°C, the heating rate is controlled at 3°C / min. After the temperature reaches 70°C, the heating is stopped and the temperature is kept warm to obtain a sol containing zinc hydroxide and basic zinc carbonate precipitate; adding 15 parts by weight of ammonia water to the sol, letting it stand for 2-3 hours, and then drying it, and The dried product is calcined at 800°C to obtain nano zinc oxide. The preparation method of carbon black comprises the following steps: adding 40 parts by weight of ethanol to 100 parts by weight of water to obtain a dispersion; adding 8 parts by weight of quick-pressed black to the dispersion, and ultrasonically oscillating until uniformly dispersed to obtain a mixed solution C; adding 20 parts by weight of vinyltrimethoxysilane and 6 parts by weight of an organic acid to the mixed solution C, stirring evenly and reacting for 3 hours, then adjusting the pH to 7, heating in a water bath at 40°C for 5 hours, and then washing, drying, and grinding to obtain carbon black.
[0026] A method for preparing high-performance shock-absorbing rubber comprises the following steps: mixing a vitrified filler and a reinforcing agent, heating the mixture to 500°C, and heat-treating the mixture for 30 minutes, grinding the mixture to pass a 600-mesh sieve, and then treating the mixture with plasma for 3 minutes; B. firstly putting natural rubber, butadiene rubber, nano zinc oxide and adhesive resin into an internal mixer, and plasticizing the mixture at a temperature of 70°C for 8 minutes; then putting a light antioxidant, paraffin wax, carbon black, a reinforcing agent, a composite vulcanizing agent and a curing agent into the internal mixer, and plasticizing the mixture at a temperature of 120°C for 8 minutes; C. firstly putting natural rubber, butadiene rubber, nano zinc oxide and adhesive resin into an internal mixer, and plasticizing the mixture at a temperature of 70°C for 8 minutes; and finally plasticizing the mixture at a temperature of 120°C for 8 minutes. °C, mixing for 8 minutes, cooling to room temperature and discharging; C, using a double-roll mill, adding the product of step B and a flux at 63 °C, heating to 160 °C and mixing for 45 minutes, then adding the product of step A, cooling to 110 °C, vacuum mixing for 1 hour, and naturally cooling to obtain a masterbatch; D, then rolling the masterbatch in step C, after the rubber layer is smooth, adding a vulcanization accelerator and sulfur, making a triangle thin package, and mixing to obtain a mixed rubber; vulcanizing the mixed rubber at high temperature to obtain a shock-absorbing rubber.
[0027] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high-performance shock-absorbing rubber, characterized in that: The method comprises the following steps: the high-performance shock-absorbing rubber comprises the following parts by weight: 60-90 parts of natural rubber, 10-30 parts of butadiene rubber, 3-6 parts of nano zinc oxide, 2-4 parts of antioxidant, 10-13 parts of vitrified filler, 1-3 parts of paraffin wax, 15-30 parts of carbon black, 10-25 parts of reinforcing agent, 0.5-1 parts of sulfur, 1-3 parts of composite vulcanizing agent, 1-2 parts of accelerator, 1-2 parts of curing agent and 1-2 parts of adhesive resin; the reinforcing agent is serpentine powder.
2. A high performance shock absorbing rubber according to claim 1, characterized in that: The preparation method of the serpentine powder is as follows: 100 mesh serpentine powder is dispersed in deionized water at a mass ratio of 1: (3-5) of solid-liquid ratio, ultrasonically dispersed for 10-30 minutes while stirring, and then heated to 50-90° C., melamine solution is added to the slurry, and then kept warm for reaction for 5-8 minutes, and then placed in a microwave condition of 100-300W for reaction for 1-3 minutes. After the reaction is completed, the product is dried and crushed.
3. A high performance shock absorbing rubber according to claim 1, characterized in that: The preparation method of the nano zinc oxide is as follows: 8-12 parts by weight of zinc acetate and 4-8 parts by weight of zinc sulfate are added to 100 parts by weight of water, and mixed solution A is prepared after stirring and dissolving; 10-15 parts by weight of sodium carbonate or potassium carbonate are dissolved in 100 parts by weight of water, and mixed solution B is prepared after stirring and dissolving; mixed solution B is added to mixed solution A while stirring, and the adding speed of mixed solution B is controlled to be 1-2mL / min, and then the temperature is increased while stirring, in the initial stage, the heating rate is controlled to be 4-8°C / min, after the temperature reaches 55°C, the heating rate is controlled to be 1-3°C / min, after the temperature reaches 70°C, the heating is stopped, and the temperature is kept warm to obtain a sol containing zinc hydroxide and basic zinc carbonate precipitation; 10-15 parts by weight of ammonia water is added to the sol, and the sol is left to stand for 2-3h, and then dried, and the dried product is calcined at 700-800°C to obtain nano zinc oxide.
4. A high performance shock absorbing rubber according to claim 1, characterized in that: The preparation method of carbon black comprises the following steps: adding 30-40 parts by weight of ethanol to 100 parts by weight of water to obtain a dispersion; adding 4-8 parts by weight of quick-pressed black to the dispersion, and ultrasonically oscillating until uniformly dispersed to obtain a mixed solution C; adding 10-20 parts by weight of vinyltrimethoxysilane and 4-6 parts by weight of an organic acid to the mixed solution C, stirring uniformly, reacting for 2-3 hours, then adjusting the pH to 6-7, heating in a water bath at 35-40°C for 3-5 hours, and then washing, drying, and grinding to obtain the carbon black.
5. A method for preparing a high-performance shock-absorbing rubber according to claim 1, characterized in that: The method comprises the following steps: A. Mix the vitrifiable filler and reinforcing agent, heat to 500-700°C, keep warm for 30-45 minutes, grind until it passes through a 600-mesh sieve, and then use plasma treatment for 3-7 minutes; B. First, natural rubber, cis-1,4-butadiene rubber, nano zinc oxide and adhesive resin are put into an internal mixer, and plasticized at a temperature of 70 to 110°C for 8 to 20 minutes. Then, light antioxidant, paraffin wax, carbon black, reinforcing agent, composite vulcanizing agent and curing agent are put into the internal mixer, and mixed at a temperature of 120 to 140°C for 8 to 15 minutes, and then cooled to room temperature for discharge; C. Using a double-roll mill, add the product of step B and a flux at 63-68°C, heat to 160-170°C and mix for 45-50min, then add the product of step A, cool to 110-130°C, vacuum mix for 1-2h, and cool naturally to obtain a masterbatch; D. Then, the master rubber in step C is rolled, and after the rubber layer is smooth, a vulcanization accelerator and sulfur are added, and the mixture is rolled into a triangle and then rolled and mixed to obtain a rubber mixture; and the rubber mixture is vulcanized at high temperature to obtain a shock-absorbing rubber.
6. A method for preparing a high-performance shock-absorbing rubber according to claim 5, characterized in that: The process conditions of plasma treatment are: nitrogen is the treatment substance, the treatment power is 200-300W, and the nitrogen flow is 0.1-0.2NL / min.
7. A method for preparing a high-performance shock-absorbing rubber according to claim 5, characterized in that: The vacuum mixing is performed with a vacuum pressure of -0.05Mpa to -0.02Mp.
8. A method for preparing a high-performance shock-absorbing rubber according to claim 5, characterized in that: Vulcanization is carried out on a flat vulcanizing press at 170-190°C and 8-16MPa for 5-20min.